Bibliometric Analysis of Male Domination Articles Since 1958-2022 - Ahmad Hamidi; Nurus Shalihin; Amelia Permata Sari; Arwansyah bin Kirin (Journal of Techno-Social, 2024)
This article aims to analyse bibliometric-based male dominance with the keyword "male dominance" as search input. The Scopus.com web link is used in searching document databases with the type "article" about dominance studies worldwide. Bibliometric data were analysed using VOSviewer Type 1.6.18 software to visualise the network of authors, years, countries, keywords, and study depth related to the issue of male dominance. An analysis conducted on December 18, 2022, found 704 documents between 2000 and 2023. The research results show that, first, in the last six years (2017–2022), the number of publications about domination has grown significantly. Second, the United States is a country that contributes the most significant and productive number of publications in the world related to dominance studies. Third, the main keywords often used in dominance articles are women, state, murder, crime, violence, family, Islam, society, women's status, and gender. Furthermore, fourthly, the latest keywords used are relationship, west, historian, religion, Islamic law, and Christianity.